2021
DOI: 10.1021/acssuschemeng.0c07067
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis-Based Magnetic Diatoms for Biological Applications

Abstract: Here, we report the green synthesis of silica-based materials for the treatment of biological samples such as bacteria enrichment and exosome isolation. The synthesized materials were nanosized, recyclable, and magnetically separable using an eco-friendly hydrothermal synthesis approach. Fe 3 O 4 formation on the surface of biosilica porous diatomite via precipitation was used to create a magnetic diatom (mag-DE) through a bottom-up approach, which was low cost, robust, nontoxic, and eco-friendly. Following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Isolation of toxic and pathogenic bacteria using functionalized magnetic diatoms. Con A, concanavalin A. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Applications Of Diatomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of toxic and pathogenic bacteria using functionalized magnetic diatoms. Con A, concanavalin A. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Applications Of Diatomsmentioning
confidence: 99%
“…108 Additionally, the organic extracts of Chaetoceros pseudocurvisetus and Skeletonema costatum exhibited antituberculosis effects with no toxicity on normal human cell lines. 112 Impressively, Shin et al 113 have shown the biological and clinical capabilities of green-synthesized magnetic (Fe 3 O 4 ) diatoms functionalized by APTES. They were deployed for bacterial enrichment and isolation of Salmonella sp., after conjugated with concanavalin A (as micro-antimicrobial agent) and also for the exosome isolation while conjugated with precise antibody; the magnetic particles were precipitated on the surface of diatomite biosilica (Figure 15).…”
Section: Applications Of Diatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…LF was immobilized on the thiol‐modified surfaces of the MNPs by attaching it with the heterobifunctional crosslinker GMBS (Dao et al., 2021 ). Hydroxyl groups on the surface of the MNPs were converted to thiol groups by using a silanization solution of 4% (v/v) 3‐MPS overnight at room temperature, followed by washing with ethanol and incubation with 1 mM GMBS solution at room temperature for 1 h. LF was attached to the GMBS‐immobilized surface at room temperature for 1 h. The modified MNPs were immediately used or stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, antibodies are modified onto the surface of spherical magnetic beads to target the exosome antigens and achieve high-specificity of exosome capture. Although it has made remarkable progress, one should notice that biological fluids often contain a large number of non-target substances, such as cell debris, protein precipitates, large-size extracellular vesicles, etc., 19 and these substances would adsorb on the surface of the traditional spherical immunomagnetic beads non-specifically to decrease the purity of the obtained specimens, even if the antifouling components (e.g., PEG) 20 have been employed to repel possible nonspecific adsorption.…”
Section: Introductionmentioning
confidence: 99%